Mechanical properties and morphologic features of intrinsic foot muscles and plantar fascia in individuals with hallux valgus - Serkan Taş; Alp Çetin (Acta Orthopaedica et Traumatologica Turcica, 2019)
Background: The aim of the present study was to investigate the morphologic features and mechanical properties of plantar fascia (PF), flexor hallucis brevis (FHB), flexor digitorum brevis (FDB), and abductor hallucis (AbH) muscles in individuals with halluks valgus (HV) and to compare the results with individuals without HV. Methods: A total of 30 participants (27 female, 3 male) between the ages of 19–58 years with HV deformity and 30 individuals without HV (27 female, 3 male) between the ages of 20–58 years were included in the study. AbH, PF, FHB, and FDB thickness, cross-sectional area and stiffness were measured with an ultrasonography device. For stiffness measurements, Shear Wave Velocity (SWV) of the assessed soft tissues was calculated using a customized software program. Results: Mean and standard deviation of SWV of PF, AbH, FHB, FDB, and thickness of PF, AbH, FHB, FDB, and cross-sectional area of AbH, FHB, FDB in individuals with HV were 7.6 ± 1.0 m/sec, 2.8 ± 0.3 m/sec, 2.6 ± 0.4 m/sec, and 3.4 ± 0.2 m/sec, 3.3 ± 0.5 mm, 11.4 ± 2.2 mm, 16.5 ± 1.9 mm, 8.9 ± 1.8 mm, 2.4 ± 0.5 cm2, 2.7 ± 0.5 cm2, 1.9 ± 0.6 cm2, respectively. Mean and standard deviation of SWV of PF, AbH, FHB, FDB and thickness of PF, AbH, FHB, FDB, and cross-sectional area of AbH, FHB, FDB in controls groups were 7.6 ± 1.2 m/sec, 2.3 ± 0.3 m/sec, 2.3 ± 0.4 m/sec, and 3.4 ± 0.4 m/sec, 3.3 ± 0.5 mm, 9.7 ± 2.1 mm, 14.5 ± 1.4 mm, 9.7 ± 1.2 mm, 2.1 ± 0.3 cm2, 2.3 ± 0.4 cm2, 2.1 ± 0.4 cm2, respectively. Individuals with HV had lower AbH and FHB thickness, cross-sectional area and SWV, however FDB thickness and cross-sectional area were higher in individuals with HV compared to that of individuals without HV (p < 0.05). PF thickness (p = 0.273), SWV of PF (p = 0.979) and FDB (p = 0.295) were similar in both groups. Conclusion: Our results suggest that individuals with HV had lower AbH and FHB stiffness, however PF and FDB stiffness were similar in HV and control group. In addition, AbH and FHB thickness and cross-sectional area were lower in individuals with HV; however, FDB thickness and cross-sectional area were higher in individuals with HV compared to that of individuals without HV. Level of Evidence: Level III, Diagnostic Study. Keywords: Hallux valgus, Foot muscles, Stiffness, Muscle size, Ultrasonography, Sonoelestography